Impact of Intrinsic and Extrinsic Gaming Elements on Online Purchase Intention - Wu, Xiaomei; Santana, Silvia (Frontiers in Psychology, 2022)
Gamification is a developing trend that can work on customers' motivation and performance in online business areas. Notwithstanding, it is still vigorously debated as there is a continuous conversation inside the gamification community about whether individual gamification elements may really weaken or improve on customers' intrinsic and extrinsic motivations as well as the effect on the consumer's perceived enjoyment and purchase intention. The study uses a questionnaire survey as the research method. A total of 310 questionnaires were distributed, and after the data screening, 302 sets were valid data. The data analysis for this study was analyzed by using SPSS and Smart-PLS. The findings of this study show that intrinsic and extrinsic gaming elements affect consumers' purchase intention in gamification. This study shows how extrinsic gaming elements such as points, badges, feedback and challenges are affecting customers' perceived enjoyment. Furthermore, intrinsic gaming elements such as leaderboards, levels, avatars, and privacy control are affecting customers' perceived enjoyment. It also shows that perceived enjoyment positively affects purchase intention and mediates the relationship between intrinsic and extrinsic gaming elements and purchase intention. Additionally, it shows that promotion focus negatively moderates the relationship between intrinsic elements and perceived enjoyment. This study presents a new research model to explore the effect of extrinsic and intrinsic elements in gamification on purchase intention. The results of this research may help game designers to identify the right design features for the right customers, which has important practical implications for online business development.